2012
DOI: 10.11564/26-1-221
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of contraceptive use among HIVdiscordant couples in Kenya

Abstract: Despite risks of HIV transmission to infants born of the HIV positive women, contraceptive use is uncommon among women in HIV discordant Additionally, being married (OR 2.4,, attending Thika site clinic (OR 6.1,, and having two or more children (OR 1.9, were significantly associated with use of non barrier contraceptives. Future programs should focus on interventions to increase contraceptive use among HIV serodiscordant couples, with a special emphasis on HIV negative women, unmarried women and women with few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…We estimated a sample size of 283 women would be required using Cochrane’s formula for a single proportion and estimatingthe proportion of HIV- infected women who used dual contraception was 24.3% [ 27 ], assuming a 95% confidence interval and 5% level of significance. Sampling was done in two stages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated a sample size of 283 women would be required using Cochrane’s formula for a single proportion and estimatingthe proportion of HIV- infected women who used dual contraception was 24.3% [ 27 ], assuming a 95% confidence interval and 5% level of significance. Sampling was done in two stages.…”
Section: Methodsmentioning
confidence: 99%
“…Relationship factors like communication between partners and partner approval can influence decisions on whether or not to continue dual method use [ 6 , 23 , 25 ]. In Kenya, dual contraception use is uncommon, as suggested from studies that have indicated that over-reliance on male condom, coupled with inconsistent use, has led to high levels of unintended pregnancies [ 26 , 27 ]. In addition, Kenya has had a steady increase in pregnancy rates among HIV-infected mothers [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study (Daniele, 2017) alluded to the potential differences in men's willingness to engage with FP when they were in a monogamous versus polygamous marriage, with the latter proposed as leading to less investment in the healthcare of each wife. HIV status was mentioned as a key factor in two studies, with both noting that HIV positive status was associated with increased contraceptive use (Mantell et al, 2014;Ngure et al, 2012).…”
Section: The Effects Of Male Engagement Interventions On Contraceptiv...mentioning
confidence: 99%